STRATEGIC THINKING AS A CORE COMPETENCY FOR BUSINESS SUSTAINABILITY - Azizan, Norizan Haji; Othman, Siti Zubaidah; Yusoff, Rushami Zien (CENTRAL ASIA AND THE CAUCASUS, 2021)
Change is a dynamic force that is part of business and managerial life. To ensure business sustainability and survival in today’s volatile, uncertain, complex and ambiguous (VUCA) environment, organizations need pro-active managers with strategic thinking competency to foresee and plan beyond the current business scenario. Strategic thinking competency is identified as a critical skill to predict the environment accurately and remain competitive in an increasingly unstable business environment. Nevertheless, many managers lack this skill. Thus, managers must continuously learn to become competent and to be able to cope in this environment. The main purpose of this qualitative study was to examine learning experiences which contributed to the development of strategic thinking competency amongst managers in Malaysia. Adopting grounded theory methodology, semi-structured interviews were conducted amongst 25 managers. Theoretical sampling and constant comparative method were utilized to identify major categories and themes. Every category and occurrence were analysed and compared to find significant connections among them. Three general themes were identified: formal & informal learning, individual factors, and organizational factors. It was found that managers developed strategic thinking competency through a fusion of various learning experiences. These themes provided some insights into the significance of learning experiences in the development of strategic thinking competency based on the participants’ perceptions. The study also proposed that strategic thinking is the foundation of strategic planning and strategic management. Organizations must play a more active role in developing strategic thinkers should they want to survive and succeed in the uncertain times ahead.